1992
DOI: 10.1111/j.1365-2230.1992.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of amorolfine nail lacquer 5% in onychomycosis, once-weekly versus twice-weekly

Abstract: Amorolfine is a new topical antifungal of the phenylpropyl morpholine class which is highly active both in vitro and in vivo against yeasts, dermatophytes and moulds responsible for superficial fungal infections. Human pharmacological studies have established that amorolfine has a persistent antifungal effect in the nail bed and in the skin without being systemically absorbed. This has been confirmed by clinical work showing that amorolfine is effective in treating dermatomycoses and onychomycoses when adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 6 publications
2
48
1
Order By: Relevance
“…A sample size of 120 patients (60 patients per group) was deemed necessary to detect a 14% difference in success rate between the two treatment groups based on the results of previous 136 studies [12,15] , where P-3051 and amorolfine achieved the efficacy parameter in 80 and 66% of patients, respectively. Assuming a screening failure rate of 30% of patients displaying negative fungal culture, about 160 patients had to be selected for screening.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A sample size of 120 patients (60 patients per group) was deemed necessary to detect a 14% difference in success rate between the two treatment groups based on the results of previous 136 studies [12,15] , where P-3051 and amorolfine achieved the efficacy parameter in 80 and 66% of patients, respectively. Assuming a screening failure rate of 30% of patients displaying negative fungal culture, about 160 patients had to be selected for screening.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It has been reported that the clinical cure rate for 5% amorolfine nail lacquer was 38 to 52% (14,18), and that of 8% ciclopirox nail lacquer was 8% (7). When each rate of culture positivity in the drug-treated groups was subtracted from that in the nontreated group, the differences were 54.2% for 5% amorolfine nail lacquer and 8.3% for 8% ciclopirox nail lacquer.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for evaluating efficacy in clinical trials used to be the main explanation of differences in results from study to study. Examples can be found in the evaluation of the efficacy of amorolfine between the pivotal study [2], reporting clinical and mycological cure in 45–51% of patients, and a more recent controlled randomized trial with the same drug [3], which reported a cure rate of < 1% in an apparently similar patient population, with a similar treatment schedule. Other examples can be found in the literature for ciclopirox (CPX) [4] between the US pivotal studies and non-US studies.…”
Section: Introductionmentioning
confidence: 99%